Gender and a "colonialtairian" digital society - Political effects of women's and feminist organizations' usage of the Internet within the context of male and "colonialtairian" domination: the cases of South Africa and Senegal - (:unkn) unknown (My University, 2011)
With our initial intention to be liberated from the definitions -- technical, technocratic or those emanating from the sociology of the social appropriation of ICT uses -- in order to analyze the usage of the Internet in women's and feminist organizations in Africa, we focused in this thesis on theoretical work relating to patriarchy and the coloniality of power (totality of social relations characterized by subalternity -- hierarchization between the dominants and the dominated -- produced by the expansion of capitalism.) This position enabled us to establish a working analytical framework without imposing Western, South American or Asian theoretical analyses on Africa. It also facilitated how we expressed the problematic of the relationship between male domination and the domination inherent in the coloniality of power, which we have called "colonialtairian" in the context of globalization and hypermodernity. The differentiated manifestations of this relationship in South Africa and Senegal helped us delineate the field and context within which local women's or feminist organizations use or don't use the Internet. Comparing their representations within the conceptual framework proved edifying and indispensable in determining the politicization of their use. It thus became apparent that among the information and communication technologies, the Internet crystallizes one means by which the "Information Society" is both the product and the production of a hypermodern globalization in which the systems of coloniality of power and patriarchy function conjointly. This conjunction is clearly evidenced both theoretically and empirically. Especially noteworthy is that the epistemology used in this context reconnects to traditionalistic, nationalistic, paternalistic and male constructions of knowledge echoing what this tool facilitates: a rapid increase of the appropriation of women's bodies, the dominants' rhetorical and political grandstanding, the institutio
Keywords: African Research